Analysis of The Reward and Punishment System on Employee Performance at PT The Univenus - Sunarto Budiono; Sopiah Sopiah; Arief Noviarakhman Zagladi (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2026)
Objective: This study aims to analyse the effect of implementing a reward and punishment system on employee performance at PT The Univenus. Method: The research utilised a quantitative approach with a survey method. The research sample consisted of employees of PT The Univenus selected using purposive sampling. Data were collected through questionnaires, which were then analysed using SEM-PLS with the aid of software. Results: Research results indicate that the reward and punishment system has a significant impact on employee performance. The reward variable is positively correlated with increased motivation and work productivity, while punishment serves as an effective behavioural control mechanism. However, the study also identifies that the effectiveness of the system highly depends on proportionate and fair implementation. Novelty: The novelty of this research lies in the integration of reward and punishment system analysis on employee performance in the context of the tissue paper manufacturing industry, which not only tests direct effects but also captures the dynamics of the relationships between variables more predictively.